2021
DOI: 10.1002/chem.202102418
|View full text |Cite
|
Sign up to set email alerts
|

Are Heavy Pnictogen‐π Interactions Really “π Interactions”?

Abstract: The noncovalent interactions of heavy pnictogens with π‐arenes play a fundamental role in fields like crystal engineering or catalysis. The strength of such bonds is based on an interplay between dispersion and donor/acceptor interactions, and is generally attributed to the presence of π‐arenes. Computational studies of the interaction between the heavy pnictogens As, Sb and Bi and cyclohexane, in comparison with previous studies on the interaction between heavy pnictogens and benzene, show that this concept p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…Compared to the other widely used functionals (e.g. TPSS and PBE), which in their corrected versions accurately describe interaction energies and their components in agreement with previous studies, 30,[32][33][34] PBE0 has shown a reasonable accuracy on both, dispersive and non-dispersive (electrostatic, chargetransfer and covalent) contributions (for more details, see ESI †).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Compared to the other widely used functionals (e.g. TPSS and PBE), which in their corrected versions accurately describe interaction energies and their components in agreement with previous studies, 30,[32][33][34] PBE0 has shown a reasonable accuracy on both, dispersive and non-dispersive (electrostatic, chargetransfer and covalent) contributions (for more details, see ESI †).…”
Section: Resultssupporting
confidence: 86%
“…Note that an in-depth analysis of the nature of the interaction has been published previously. 33,34 Moving down the group, the 'Top Y' structure becomes more favorable with respect to the others, leading to a presumed crossover of the most stable crystal structure around Sb.…”
Section: Papermentioning
confidence: 99%
“…21 It hinders the study for resolving the structure−property− performance relationships of organic photocatalysts. 22,23 An organic photocatalyst constructed via noncovalent bond interactions between organic molecules with a conjugated structure 24 not only exhibits the most advantages of organic semiconductor materials 25,26 but also possesses a precise and controllable synthesis process. 27,28 Among them, employing polycyclic aromatic hydrocarbon as the main skeleton to build organic photocatalyst is a promising strategy due to the extended conjugated structure favoring charge transport.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the most organic photocatalysts, , the synthetic methods are limited and the exact structures are not clear due to the difficulty controlling the construction of covalent bonds . It hinders the study for resolving the structure–property–performance relationships of organic photocatalysts. , An organic photocatalyst constructed via noncovalent bond interactions between organic molecules with a conjugated structure not only exhibits the most advantages of organic semiconductor materials , but also possesses a precise and controllable synthesis process. , Among them, employing polycyclic aromatic hydrocarbon as the main skeleton to build organic photocatalyst is a promising strategy due to the extended conjugated structure favoring charge transport. Particularly, pyrene-based molecules exhibit excellent electronic and optical physical properties and especially excellent thermal , and photochemical stabilities in both solution and solid states, making it potentially used as the molecular unit for designing a new self-assembled organic photocatalyst . However, only a few self-assembled organic photocatalysts have been fabricated due to the challenge of finding suitable units to achieve π–π stacking interactions via a self-assembly process .…”
Section: Introductionmentioning
confidence: 99%
“…PnBs are involved in numerous chemical functions such as the capture and transport of halides across a phospholipid membrane [ 25 ]. They can reverse the energetic balance between the chair and twist-boat conformations of cyclohexane [ 26 ]. The PnB is often involved in catalysis [ 27 , 28 ]: some examples include a chiral scaffold [ 29 ], enantioselective transfer hydrogenation of benzoxazines [ 30 ], and polyether cascade cyclizations [ 31 ].…”
Section: Introductionmentioning
confidence: 99%